Current controversies in determining the main mechanisms of atrial fibrillation. (16th March 2016) - Schotten, U.; Dobrev, D.; Platonov, P. G.; Kottkamp, H.; Hindricks, G.
Abstract: Despite considerable basic research into the mechanisms of atrial fibrillation (AF), not much progress has been made in the prognosis of patients with AF. With the exception of anticoagulant therapy, current treatments for AF still do not improve major cardiovascular outcomes. This may be due partly to the diverse aetiology of AF with increasingly more factors found to contribute to the arrhythmia. In addition, a strong increase has been seen in the technological complexity of the methods used to quantify the main pathophysiological alterations underlying the initiation and progression of AF. Because of the lack of standardization of the technological approaches currently used, the perception of basic mechanisms of AF varies widely in the scientific community. Areas of debate include the role of Ca 2+ ‐handling alterations associated with AF, the contribution and noninvasive assessment of the degree of atrial fibrosis, and the best techniques to identify electrophysiological drivers of AF. In this review, we will summarize the state of the art of these controversial topics and describe the diverse approaches to investigating and the scientific opinions on leading AF mechanisms. Finally, we will highlight the need for transparency in scientific reporting and standardization of terminology, assumptions, algorithms and experimental conditions used for the development of better AF therapies. Abstract : Content List – Read more articles from the symposium: Atrial fibrillation ‐ from atrial extrasystoles to atrial cardiomyopathy. What have we learned from basic science and interventional procedures